2019
DOI: 10.1039/c9nj02913c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and improving photoelectrochemical performance of Bi2O3/Bi2S3 composite

Abstract: The simple and fast ultrasonic-assisted synthesis of high-performance, low-interfacial-resistance Bi2O3/Bi2S3 composite semiconductors is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It has been shown that Bi 2 S 3 coupled with TiO 2 or Bi 2 O 2 CO 3 to form Bi 2 S 3 –TiO 2 and Bi 2 S 3 –Bi 2 O 2 CO 3 heterogeneous systems demonstrates enhanced photoactive performance for photosensitive device applications. , Furthermore, Bi 2 O 3 -based heterogeneous systems such as Bi 2 O 3 –BiOCl, CuBi 2 O 4 –Bi 2 O 3 , and TiO 2 –Bi 2 O 3 all demonstrate improved photoactive performance compared with their single constituent counterparts. ,, Based on the above discussion, it might be interesting to integrate Bi 2 S 3 with Bi 2 O 3 to form a heterogeneous system and investigate the photoactive performance of this hybrid system. A well-defined Bi 2 O 3 –Bi 2 S 3 composite has been synthesized using an ultrasonic-assisted synthetic method on a conductive substrate, and the resulting Bi 2 O 3 –Bi 2 S 3 composite shows highly enhanced photoelectrochemical activity . Branched Bi 2 O 3 –Bi 2 S 3 composites synthesized by a simple hydrothermal method without toxic substances demonstrate high photocatalytic activity under visible-light illumination .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Bi 2 S 3 coupled with TiO 2 or Bi 2 O 2 CO 3 to form Bi 2 S 3 –TiO 2 and Bi 2 S 3 –Bi 2 O 2 CO 3 heterogeneous systems demonstrates enhanced photoactive performance for photosensitive device applications. , Furthermore, Bi 2 O 3 -based heterogeneous systems such as Bi 2 O 3 –BiOCl, CuBi 2 O 4 –Bi 2 O 3 , and TiO 2 –Bi 2 O 3 all demonstrate improved photoactive performance compared with their single constituent counterparts. ,, Based on the above discussion, it might be interesting to integrate Bi 2 S 3 with Bi 2 O 3 to form a heterogeneous system and investigate the photoactive performance of this hybrid system. A well-defined Bi 2 O 3 –Bi 2 S 3 composite has been synthesized using an ultrasonic-assisted synthetic method on a conductive substrate, and the resulting Bi 2 O 3 –Bi 2 S 3 composite shows highly enhanced photoelectrochemical activity . Branched Bi 2 O 3 –Bi 2 S 3 composites synthesized by a simple hydrothermal method without toxic substances demonstrate high photocatalytic activity under visible-light illumination .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, VI-bismuth materials Bi2X3 are functional compounds [3] and very attractive materials for several applications including: photovoltaics [4], thermoelectrics [5], photoelectrochemicals [6] , photocatalytic activity [7] , micro-and optoelctronic devices [8] and infrared detectors [9]. Among Bi2X3 materials, the bismuth sulfide 𝐵𝑖 2 𝑆 3 -bismuthiniteis a metal chalcogenide with a very attractive and intriguing properties : a large optical absorption coefficient (> 10 5 𝑐𝑚 −1 for 𝜆 < 500 𝑛𝑚), high electron mobility (> 500 𝑐𝑚 𝑉 −1 𝑠 −1 ) [10] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, VI-bismuth materials Bi2X3 are functional compounds [3] and very attractive materials for several applications including: photovoltaics [4], thermoelectrics [5], photoelectrochemicals [6] , photocatalytic activity [7] , micro-and optoelctronic devices [8] and infrared detectors [9]. Among Bi2X3 materials, the bismuth sulfide 2 3 -bismuthiniteis a metal chalcogenide with a very attractive and intriguing properties : a large optical absorption coefficient (> 10 5 −1 for < 500…”
Section: Introductionmentioning
confidence: 99%